Caffeine-catalyzed gels. (July 2018) - DiCiccio, Angela M.; Lee, Young-Ah Lucy; Glettig, Dean L.; Walton, Elizabeth S.E.; de la Serna, Eva L.; Montgomery, Veronica A.; Grant, Tyler M.; Langer, Robert; Traverso, Giovanni
Abstract: Covalently cross-linked gels are utilized in a broad range of biomedical applications though their synthesis often compromises easy implementation. Cross-linking reactions commonly utilize catalysts or conditions that can damage biologics and sensitive compounds, producing materials that require extensive post processing to achieve acceptable biocompatibility. As an alternative, we report a batch synthesis platform to produce covalently cross-linked materials appropriate for direct biomedical application enabled by green chemistry and commonly available food grade ingredients. Using caffeine, a mild base, to catalyze anhydrous carboxylate ring-opening of diglycidyl-ether functionalized monomers with citric acid as a tri-functional crosslinking agent we introduce a novel poly(ester-ether) gel synthesis platform. We demonstrate that biocompatible Caffeine Catalyzed Gels (CCGs) exhibit dynamic physical, chemical, and mechanical properties, which can be tailored in shape, surface texture, solvent response, cargo release, shear and tensile strength, among other potential attributes. The demonstrated versatility, low cost and facile synthesis of these CCGs renders them appropriate for a broad range of customized engineering applications including drug delivery constructs, tissue engineering scaffolds, and medical devices.